Legal Liability for Uploading Movie Spoilers on Social Media Instagram and Youtube Based on Indonesian Law - Faradila Harahap; OK. Saidin; Jelly Leviza; T. Keizerina Devi Azwar (LOCUS MEDIA PUBLISHING, 2023)
The purpose of this writing is to know and analyze the violation of uploading spoilers for other people's copyrighted works according to Law Number 28 of 2014 concerning Copyright; forms of copyright infringement for uploading movie spoilers on social media Instagram and YouTube; and legal liability for uploading movie spoilers on social media. This type of research is normative research and descriptive in nature. The data source comes from secondary data consisting of primary, secondary, and tertiary legal materials obtained through document study data collection techniques. The results of the study concluded that the act of mutilation of creation in movie spoilers is an infringement of copyright because it eliminates part of the creation or work of the creator of a movie. Forms of copyright infringement on the act of uploading movie spoilers are mostly done without the permission of the copyright holder and are rampant on social media services such as Instagram, and YouTube. Legal liability for uploading movie spoilers on social media can be held civilly liable under Article 1365 of the Civil Code and criminal liability as in Law No. 28 of 2014 on copyright.